Survey of financial charcaterisitcs of consumers - Projector, S. Dorothy; Weiss S. Gertrude (United State Governors of the federal reserve system, 1966)
This book reveals survey done to examine the financial characteristics of consumers in the United State market. It was conducted using the 1963 census interviewers and other special agents to arrived at their findings.
asm; 05/03/19
Loans
Keywords: Economy history; consumers; United States